Generation and analysis of an Eucalyptus globulus cDNA library constructed from seedlings subjected to low temperature conditions - Rasmussen-Poblete,Susana (Pontificia Universidad Católica de Valparaíso, 2008)
Eucalyptus globulus is the most important commercial temperate hardwood in the world because of its wood properties and due to its characteristics for biofuel production. However, only a very low number of expressed sequence tags (ESTs) are publicly available for this tree species. We constructed a cDNA from E. globulus seedlings subjected to low temperature and sequenced 9,913 randomly selected clones, generating 8,737 curated ESTs. The assembly produced 1,062 contigs and 3,879 singletons forming a Eucalyptus unigene set. Based on BLASTX analysis, 89.3% of the contigs and 88.5% of the singletons had significant similarity to known genes in the non-redundant database of GenBank. The Eucalyptus unigene set generated is a valuable public resource that provides an initial model for genes and regulatory pathways involved in cell wall biosynthesis at low temperature.